2017
DOI: 10.1080/17843286.2017.1336294
|View full text |Cite
|
Sign up to set email alerts
|

Impact of purchasing the CPAP device on acceptance and long-term adherence: a Belgian model

Abstract: CPAP reimbursement influences the purchase of CPAP but once the device becomes available there is no difference with reimbursed patients in long-term adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In our study, only fatigue was an independent predictor for good CPAP compliance. A previous study from Belgium showed that fatigue was also a predictor for CPAP purchase with a coefficient of 0.538 ( p=0.008) [18]. Additionally, fatigue is a common symptom of OSA, resulting in the limitation of physical activity and/or poor quality of life [19].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only fatigue was an independent predictor for good CPAP compliance. A previous study from Belgium showed that fatigue was also a predictor for CPAP purchase with a coefficient of 0.538 ( p=0.008) [18]. Additionally, fatigue is a common symptom of OSA, resulting in the limitation of physical activity and/or poor quality of life [19].…”
Section: Discussionmentioning
confidence: 99%
“…A widely recognized definition of good compliance to PAP therapy is PAP device usage for an average of 4 hours per night for ≥70% of the monitoring days [ 7 ]. Cost-related issues are significant barriers to PAP compliance that are directly affected by the national insurance coverage system applied to PAP therapy [ 8 - 10 ]. In South Korea (hereafter, Korea), before July 2018, patients with OSA requiring PAP therapy had to purchase or rent the PAP device at their own expense.…”
Section: Introductionmentioning
confidence: 99%